2016
DOI: 10.1080/17483107.2016.1229048
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality avatar interaction (VRai) platform to assess residual executive dysfunction in active military personnel with previous mild traumatic brain injury: proof of concept

Abstract: The present findings show proof of concept for using avatars, particularly more interactive avatars, to expose differences in executive functioning when applying context-specific protocols (here for the military). Implications for rehabilitation Virtual reality provides a means to control context-specific factors for assessment and intervention. Adding human interaction and agency through avatars increases the ecologic nature of the virtual environment. Avatars in the present application of the Virtual Reality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…To overcome this issue, virtual reality (VR) represents an interesting alternative in order to expose individuals with disabilities to different scenarios simulating community walking [30]. The acceptability and feasibility of using VR-based assessment and training have been previously demonstrated in diverse populations with physical limitations [30][31][32]. In regard to dual-task assessment, this technology may enable the development of standard DT assessment protocols in meaningful simulated environments [30].…”
mentioning
confidence: 99%
“…To overcome this issue, virtual reality (VR) represents an interesting alternative in order to expose individuals with disabilities to different scenarios simulating community walking [30]. The acceptability and feasibility of using VR-based assessment and training have been previously demonstrated in diverse populations with physical limitations [30][31][32]. In regard to dual-task assessment, this technology may enable the development of standard DT assessment protocols in meaningful simulated environments [30].…”
mentioning
confidence: 99%
“…Besnard et al ( 25 ) created a virtual kitchen to assess daily-life activity and evaluate executive dysfunctions in subjects with severe TBI. Robitaille et al ( 26 ) developed a VR avatar interaction platform to assess residual executive functions in subjects with mild TBI. The platform can capture real-time subject’s movements translating them in to a virtual body, that is, therefore placed in a simulated environment (i.e., a village).…”
Section: Virtual Reality (Vr) For Rehabilitation After Tbimentioning
confidence: 99%
“…Time is a key issue in TBI, with a window of vulnerability and opportunity that appears much wider than previously thought: this provides an incentive to look for continuous long-lasting therapeutic interventions to interfere with neurodegenerative processes and promote regeneration. From this viewpoint, VR offers a new strategy to boost and amplify restorative processes in the clinical setting at early stages of the disease, and in daily life at later stages ( 26 ). As discussed, VR allows the development of real-life, context-specific experiences, requiring the control of the individual over different cognitive sensorimotor, and social factors, which are usually difficult to reproduce in a clinical setting.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…They found that VR was effective as a social training device, yielding improvements on various measures. Robitaille et al (2016) investigated how participants with and without post-traumatic brain injuries responded to VR avatar simulations. The researchers used a sample of 12 people in the military, 6 with injury and 6 without in a controlled experiment.…”
Section: Prior Workmentioning
confidence: 99%